(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2013)
This study was conducted in Faridpur Medical College Hospital, Faridpur, from January 2008 to December 2008 among fifty patients, diagnosed as a case of molar pregnancy. Incidenc of molar pregnancy was 8.27 per thousand pregnancy. Sixty percent of the patients were multiparous and eighty percent of low socio economic status . B positive blood group was prevalent (36%) in this study.Sixty percent( 60%) of the patients presented with amenorrhoea and abnormal vaginal bleeding.. Most of the patients (72%) were treated with suction evacuation and curettage. Of them hemorrhage was the most common immediate complication (80%). Complication like shock and perforation during evacuation was 14% and 4% respectively. Three patient (6%) developed Persistent Gestational Trophoblastic Disease(GTD) and one (2%) patient developed choriocarcinoma with lung metastasis and died. Thirty two (64%) patients attended for regular follow up but ten patients (20%) had attended irregularly and eight patients (16%) had dropped out .This study shows that follow up for molar pregnancy cases is not satisfactory in a district medical college hospital.Further improvement can be done by increasing awareness of the patients. DOI: http://dx.doi.org/10.3329/bjog.v25i2.13741 Bangladesh J Obstet Gynaecol, 2010; Vol. 25(2) : 59-64